Program Mengelola Sampah Terpadu Pada Desa Ciburial Kecamatan Cimenyan Kabupaten Bandung - Thiang Makrifat; Prasmita Dian Wijayati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Waste management in Ciburial Village, Cimenyan District, Bandung Regency still faces various challenges. Waste produced by households is usually processed individually, such as burning or landfilling it with soil. However, this method is still not effective because urban communities have limited space. Other waste management is on a paid basis, where the rubbish will be picked up by the rubbishman at each house and will end up in the final disposal site. The mass use of non-degradable and uncontrolled items, as well as deficiencies in waste processing and management, have negative implications for health and the environment. Efficient and environmentally friendly waste management is an urgent problem, and we are making every effort to bring this problem to light. Efficient and environmentally friendly waste management is an urgent need, and we are making every effort to bring attention to this problem. We want to spread our efforts and bring attention to the need for sustainable waste management by visiting every community in RT 1, RT 2, and RT 3. This qualitative descriptive research aims to detect, characterize, and explain PSAT in Ciburial Village. , Cimenyan District, Bandung Regency. Environmentally conscious volunteers and authorities from the Ciburial Community Group, Cimenyan District, Bandung Regency and other local organizations took part in this research. Apart from living in Ciburial Village, they are also active in the integrated waste management program. The findings from this research highlight the potential of integrated waste management initiatives to educate the general public about the importance of responsible waste disposal. More and more people are realizing that sustainable waste management and sorting waste for reprocessing based on type is very important. Organic waste will later be collected and reprocessed into compost, while dry waste will end up in final disposal sites.